2018
DOI: 10.1073/pnas.1710849115
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of gamma-glutamyl transferase 1 activity in the metabolic pathogenesis of chromophobe renal cell carcinoma

Abstract: SignificanceThe mechanisms of chromophobe renal cell carcinoma (ChRCC) pathogenesis remain a key knowledge gap. Through metabolomics, this study uncovered a fundamental metabolic mechanism underlying the pathogenesis of ChRCC, with key therapeutic implications for this rare tumor type, for which there are currently no specific targeted therapies. Further understanding of the impact of glutathione salvage pathway on mitochondrial function, tumor progression, and targeted therapy can provide insight into other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 33 publications
12
57
0
Order By: Relevance
“…We found that the expression of genes in glutathione (GSH) metabolism was dysregulated in RCC, which can affect the GSH levels and sensitivity to the oxidative stress. Our observations are consistent with recent studies focusing on glutathione metabolism in KICH 28,29 . We also observed that the pentose phosphatase pathway genes were upregulated in RCC.…”
Section: Discussionsupporting
confidence: 94%
“…We found that the expression of genes in glutathione (GSH) metabolism was dysregulated in RCC, which can affect the GSH levels and sensitivity to the oxidative stress. Our observations are consistent with recent studies focusing on glutathione metabolism in KICH 28,29 . We also observed that the pentose phosphatase pathway genes were upregulated in RCC.…”
Section: Discussionsupporting
confidence: 94%
“…The most strikingly increased set of metabolites in chRCC were those involved in glutathione metabolism (GSH, GSSG, γ-glutamyl-cysteine, Figure 2). This is similar to those previously identified in chRCC (Priolo et al, 2018), renal oncocytomas (Gopal et al, 2018;Kurschner et al, 2017), and in ccRCC (Hakimi et al, 2016;Wettersten et al, 2015). Since GSH is an important ROS scavenger (Circu and Aw, 2008) the increased GSH levels and GSH/GSSG ratios in chRCC can thus be considered as the main strategy for the tumor to overcome ROS stress originating from a dysregulated respiratory chain.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, metabolome profiling in chRCC revealed an impairment of the gamma-glutamyl transferase 1 activity and significantly increased levels of reduced and oxidized glutathione in chRCC (Priolo et al, 2018). A similar rewiring of the glutathione metabolism was also identified in renal oncocytomas (Gopal et al, 2018;Kurschner et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The most strikingly increased set of metabolites in pRCC were those involved in glutathione metabolism (GSH, GSSG, cysteine-glutathione disulfide, ophthalmic acid). This is similar to those previously identified in renal oncocytomas (17,55) and chRCC (27,56). GSH is an important ROS scavenger (57) and frequently produced by several tumor types to withstand unusual levels of oxidative stress (22).…”
Section: Discussionsupporting
confidence: 86%